2006
DOI: 10.1128/jb.188.7.2578-2585.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Regulation of the Bacillus subtilis glnRA and tnrA Genes Provides Evidence for DNA Binding Site Discrimination by GlnR and TnrA

Abstract: Two Bacillus subtilis transcriptional factors, TnrA and GlnR, regulate gene expression in response to changes in nitrogen availability. These two proteins have similar amino acid sequences in their DNA binding domains and bind to DNA sites (GlnR/TnrA sites) that have the same consensus sequence. Expression of the tnrA gene was found to be activated by TnrA and repressed by GlnR. Mutational analysis demonstrated that a GlnR/ TnrA site which lies immediately upstream of the ؊35 region of the tnrA promoter is req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
79
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 45 publications
4
79
0
Order By: Relevance
“…GlnR binds cooperatively to the two operators located in the glnRA promoter ( Fig. 2A) (21,22). A faint intermediately shifted band is observed in the EMSA experiments and is most readily apparent when FBI-GS is present (Fig.…”
Section: Fbi-gsmentioning
confidence: 91%
See 3 more Smart Citations
“…GlnR binds cooperatively to the two operators located in the glnRA promoter ( Fig. 2A) (21,22). A faint intermediately shifted band is observed in the EMSA experiments and is most readily apparent when FBI-GS is present (Fig.…”
Section: Fbi-gsmentioning
confidence: 91%
“…Although GlnR is the major regulator of glnA expression, the TnrA regulon is comprised primarily of genes required for the utilization of alternative nitrogen sources (3,22). Previous studies have shown that as bacterial growth becomes progressively more nitrogenrestricted, GS expression is derepressed before the pathways for the catabolism of nitrogen-containing compounds are expressed at high levels (8,34,35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GlnR. GlnR is responsive to the concentration of glutamate, glutamine, and ammonium in the growth medium (239). The carbon skeleton of glutamate and glutamine is the TCA cycle intermediate ␣-ketoglutarate.…”
Section: Regulators Responding To Tca Cycle-associated Metabolomic Chmentioning
confidence: 99%